1994
DOI: 10.1152/ajpcell.1994.266.5.c1421
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-activated, ryanodine-sensitive, IP3-insensitive Ca2+ release channels in longitudinal muscle of intestine

Abstract: We have previously shown that Ca2+ mobilization in longitudinal muscle is not mediated by inositol 1,4,5-trisphosphate (IP3) and depends on an obligatory influx of Ca2+. The present study examined whether Ca2+ influx activates ryanodine-sensitive Ca2+ channels to cause Ca(2+)-induced Ca2+ release. Ryanodine bound with high affinity to longitudinal muscle cells [dissociation constant (Kd) 7.3 +/- 0.3 nM] and microsomes (Kd 7.5 +/- 0.4 nM) and induced concentration-dependent 45Ca2+ efflux [50% effective concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
45
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 35 publications
8
45
0
Order By: Relevance
“…In longitudinal muscle cells, as previously noted herein, agonist-mediated activation of cPLA 2 and generation of arachidonic acid are the triggers for Ca 21 mobilization and initial muscle contraction (Murthy et al, 1991(Murthy et al, , 1995Kuemmerle et al, 1994Kuemmerle et al, , 1998. Previous studies had shown that both cAMP-and cGMP-dependent protein kinases phosphorylate cPLA 2 and inhibit Ca 21 mobilization and contraction , in contrast to the augmentation of contraction induced by the catalytic subunit of PKA on release from binding to IkBa.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…In longitudinal muscle cells, as previously noted herein, agonist-mediated activation of cPLA 2 and generation of arachidonic acid are the triggers for Ca 21 mobilization and initial muscle contraction (Murthy et al, 1991(Murthy et al, , 1995Kuemmerle et al, 1994Kuemmerle et al, , 1998. Previous studies had shown that both cAMP-and cGMP-dependent protein kinases phosphorylate cPLA 2 and inhibit Ca 21 mobilization and contraction , in contrast to the augmentation of contraction induced by the catalytic subunit of PKA on release from binding to IkBa.…”
supporting
confidence: 57%
“…-and cyclic ADP ribose-induced Ca 21 release via ryanodine receptors/Ca 21 channels (Murthy et al, 1991(Murthy et al, , 1995Kuemmerle et al, 1994Kuemmerle et al, , 1998Murthy, 2006). There is minimal participation of G q , RGS4, and IP 3 -dependent Ca 21 release in this muscle.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Only InsP 3 R1 is known to undergo alternative splicing with two segments (Yoshida and Imai, 1997): the 15-residue-long S1 segment located in the ligand-binding domain predominantly expressed in peripheral tissues and the 40-residue long S2 segment located in the coupling domain and predominantly expressed in the nervous system. As is the case for the majority of cell types examined so far (Wilcox et al, 1993(Wilcox et al, , 1998, smooth muscle cells express multiple InsP 3 R isoforms, although some could express none, such as the longitudinal intestinal smooth muscle cells (Kuemmerle et al, 1994).…”
mentioning
confidence: 77%
“…Ca 2ϩ mobilization in longitudinal muscle is mediated by activation of cytosolic phospholipase A 2 (cPLA 2 ) and generation of arachidonic acid (AA), leading to Ca 2ϩ influx and stimulation of cyclic ADP ribose (cADPR) (30,31,39). Ca 2ϩ and cADPR act in concert to induce Ca 2ϩ release via ryanodine receptors (RYR2)/Ca 2ϩ channels (29).…”
mentioning
confidence: 99%